Teaching business ethics to Chinese undergraduate students: using the Hunt-Vitell experiential learning model. (2016) - Feng, Chen-Yu; Schein, David D.; Song, Wei; Collins, Roger
Whereas Western literature on the teaching of business ethics is extensively developed, research of the subject in a non-Western setting is somewhat limited. This study investigated the possible impact of the teaching of business ethics on the cognitive competence and decision-making processes of Chinese business undergraduate students by using the Hunt-Vitell experiential learning model. A university in the northern region of the China was selected and a qualitative study, comprising both observation and in-depth, semi-structured interviews, was undertaken. The findings revealed that taking a business ethics course could have a significant effect on students' cognitive development, but little impact on their ethical decision-making process. The study identified an inconsistency between the students' comprehension of ethical principles and their application. Their behaviour when confronted with an ethical dilemma or situation was not consistent with the ethical theories they indicated could apply. The theoretical and the practical implications and the limitations of the study are noted. Directions for future study in this area are suggested.